Efektivitas Penggunaan LKPD Konsep Mol Berbasis Inkuiri Terstruktur Dengan Penekanan Pada Tiga Level Representasi Terhadap Hasil Belajar Peserta Didik - Prastika, Y (journal of residu, 2019)
In learning chemistry, the mole concept is very importantmaterial because it examines the number of particles (atoms, molecules, and ions). One of the learning models that can be applied in this learning is structures inquiry. This study aims to reveal the level of effectiveness of structures inquiry-based moles concept worksheets with emphasis on three levels of representation on the learning outcomes of X MIA SMA students at SMA Pembanguan Laborotrium UNP. This study included quasi-experimental research with a non-equivalent control group design. The subjects of this study were students of class X MIA 1 and MIA 2. Subjects were selected using purposive sampling technique. The object of research is the learning outcomes of students. The research instrument used was the test of student learning outcomes namely the initial test (pretest) and the final test (posttest) in the form of 20 objective questions in accordance with the learning objectives. The average difference between the initial value and the final test of the experimental class (57.2) and the control class (50.57). Based on data analysis shows that the subject is normally distributed and homogeneous so that it can be carried out t-test, obtained value t ≥ t1-α that is 3.186> 1.684 then rejects Ho. This means that the experimental class learning outcomes are higher than the control class significantly. This is also supported by the experimental value of n-gain class 0.745 in the high category. Based on the data analysis shows a structured inquiry-based rate student worksheet with emphasis on three levels of representation proved to be effective against learning outcomes with a high category